2020
DOI: 10.1016/j.jvscit.2020.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Life-threatening arterioureteral fistula treatment by endovascular complete anatomic iliac artery bifurcation reconstruction

Abstract: We present an endovascular approach for anatomic reconstruction of the iliac bifurcation in life-threatening arterioureteral fistula without sacrificing the pelvic arterial vascular supply. Five consecutive patients suffering from acute onset of significant gross hematuria caused by iliac-ureteral fistula resulting from previous oncologic surgery and radiation therapy were treated by transfemoral stent graft implantation in a double-barrel technique. Iliac-ureteral pseudoaneurysm coverage succeeded in an iliac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In our experience major risk factors for developing stent thrombosis were underlying vasculopathy or advanced tumor disease with extrinsic stenosis of iliac vessels since all three patients who developed SG thrombosis had a history of pelvic malignancy with previous surgery and radiotherapy, one of them also had advanced peripheral artery disease. Massmann et al found stent thrombosis in their case series (1/5 cases, 20%) probably caused by pre-existing large tumor vessel invasion and small vessel diameters (Massmann et al, 2020 ). Although we would primarily suggest an endovascular thrombectomy attempt for SG thrombosis, our series and the experience of Massmann et al show interventional and surgical thrombectomy both to be suitable options (Massmann et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In our experience major risk factors for developing stent thrombosis were underlying vasculopathy or advanced tumor disease with extrinsic stenosis of iliac vessels since all three patients who developed SG thrombosis had a history of pelvic malignancy with previous surgery and radiotherapy, one of them also had advanced peripheral artery disease. Massmann et al found stent thrombosis in their case series (1/5 cases, 20%) probably caused by pre-existing large tumor vessel invasion and small vessel diameters (Massmann et al, 2020 ). Although we would primarily suggest an endovascular thrombectomy attempt for SG thrombosis, our series and the experience of Massmann et al show interventional and surgical thrombectomy both to be suitable options (Massmann et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…Massmann et al found stent thrombosis in their case series (1/5 cases, 20%) probably caused by pre-existing large tumor vessel invasion and small vessel diameters (Massmann et al, 2020 ). Although we would primarily suggest an endovascular thrombectomy attempt for SG thrombosis, our series and the experience of Massmann et al show interventional and surgical thrombectomy both to be suitable options (Massmann et al, 2020 ). Too maintain the risk for SG occlusions as low as possible patients should be put on single anti platelet therapy after the procedure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…IIA coil embolization prevents retrograde perfusion of the UAF through the gluteal arteries, but also lowers the risk of recurrent bleedings -eg., in cases of stulas from the proximal IIA. Embolization of the IIA alone would not be su cient for UAF treatment (Massmann et al, 2020). It is crucial to detect stula recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality associated with UAF ranges from 7 to 58%, and the clinical outcome is correlated with an early diagnosis [ 2 , 3 ]. UAF requires a rapid a multidisciplinary approach, including the expertise of the urologist, vascular surgeon, and interventional radiologist, to detect and treat this unusual disease [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%